OPTIMIZATION OF CASE MANAGER FUNCTION IN PATIENT CENTERED CARE IN STROKE PATIENTS IN REGIONAL CILACAP HOSPITAL - Nihayatul Munaa; Fitri Ardiningsih (Indonesian Journal of Health Care Management, 2020)
Background: Case management systems are applied to improve coordination of care for chronic patients and patients with complex problems. Cilacap Hospital has implemented this but the implementation needs to be optimized. One way to optimize the case manager function.Objective: To optimize the case manager function in patient centered care in stroke patients in Cilacap Hospital.Method: The type of research used is action research. Retrieval of data by in-depth interviews with case managers, focus group discussions with professional caregivers, study of complete document case manager function forms and questionnaires for ischemic stroke patients. Output evaluation is limited to the readiness of patients to face returnResults : At the diagnosing action stage, the implementation of the case manager function in Cilacap Hospital was not optimal because there was no documentation of the case manager function form, the case manager had not received case management system training, patient centered care and discharge planning. In the planning action phase, it is planned to train the case manager and the head of the room about the case management system, patient centered care, discharge planning and preparation of the case manager function form. At the taking action stage, 2 case managers were sent to take part in the case management system, patient centered care, discharge planning training and socialize to the case manager and head of the room, compiling the case manager function form. The evaluation phase for ischemic stroke patients and the results show the readiness of patients to face increased return, the study document completeness of the case manager function form is completely filled by the case manager, and discussion to find out the supporting factors and inhibiting factors for the implementation of optimization of the case manager functionConclusions : After training on case management systems, Patient Centered Care (PCC), discharge planning and implementing a case manager function form, the case manager function becomes easier and structured. Readiness of patients facing return in ischemic stroke patients increases after optimizing the case manager function.